2014
DOI: 10.1055/s-0034-1383148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Conception Method on Twin Pregnancy Course and Outcome

Abstract: !Objective: The aim of the study was to investigate the course and outcomes of twin pregnancies conceived by different methods of assisted reproduction (ART) compared to those conceived spontaneously. Methods: The study involved patients with twin pregnancies who delivered at the Ob/Gyn Clinic of the Clinical Center of Serbia over a period of three years. Patients were differentiated according to method of conception and type of ART. Age, parity, etiology of infertility, pregnancy complications, time of membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
3
20
1
Order By: Relevance
“…ART conceived twins are at significantly increased risks of preterm birth both early and late, althouhg according to majority of studes ART twins were mostly de- livered moderately preterm (32-34 GW) 2, 10 . However, the rate of preterm birth of ART conceived twins in several investigations was similar to that of spontaneously conceived ones or that very preterm deliveries even occurred more frequently in spontaneous twin pregnancies 4 . In our study, similarly, more women delivered at term than preterm (51% vs. 49%, respectively), while late preterm birth was predominant time of delivery of preterm twins (33%).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…ART conceived twins are at significantly increased risks of preterm birth both early and late, althouhg according to majority of studes ART twins were mostly de- livered moderately preterm (32-34 GW) 2, 10 . However, the rate of preterm birth of ART conceived twins in several investigations was similar to that of spontaneously conceived ones or that very preterm deliveries even occurred more frequently in spontaneous twin pregnancies 4 . In our study, similarly, more women delivered at term than preterm (51% vs. 49%, respectively), while late preterm birth was predominant time of delivery of preterm twins (33%).…”
Section: Discussionmentioning
confidence: 73%
“…Twin pregnancies, in general, are at higher risk of numerous pregnancy complications including miscarriage or preterm birth caused by a development of two fetuses instead of one 1,2 . Adverse obstetric outcome after ART might be caused by the very procedure 4 . Moreover, ART conceived twins can be at even higher risk of pregnancy complications and adverse obstetric outcomes due to maternal age, pre-existing maternal medical conditions such as polycystic ovary syndrome or thyroid diseases that are associated with miscarriages and aneuploidies [7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is no consensus when individual papers are reviewed with regards to assisted conception twins and perinatal outcome, with some demonstrating no association with preterm and low birth weight [7,8], and others reporting increased risk [9][10][11]. Other studies have concluded twins conceived by assisted methods have similar obstetric and neonatal outcomes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%